Answer:
First term = -41.
Common difference = -15.
Step-by-step explanation:
nth term: an = a1 + (n - 1)d where a = first term and d = the common difference.
-671 = a1 + (43 - 1)d
-806 = a1 +(52 - 1)d
-671 = a1 + 42d
-806 = a1 + 51d
Subtracting ( to eliminate a1):
-671 - (-806) = 42d - 51d
-9d = 135
d = -15
Substitute for d in the first equation:
-671 = a1 + 42*-15
-671 = a1 - 630
a1 = -671 + 630 = -41.
Answer:
2.92 Rounded to the 100th
Step-by-step explanation:
Can you show the mentioned diagram?
Answer: 301.44
Explanation:
V = πr^2•h
3.14•4^2 • 6
Mrs. Yin bought more turkey than chicken. I know because 0.80 is greater than 0.69